TIGRE: A new robotic spectroscopy telescope at Guanajuato, Mexico. Issue 8 (October 2014) - Schmitt, J. H. M. M.; Schröder, K.‐P.; Rauw, G.; Hempelmann, A.; Mittag, M.; González‐Pérez, J. N.; Czesla, S.; Wolter, U.; Jack, D.; Eenens, P.; Trinidad, M. A.
Abstract TIGRE is a new robotic spectroscopy telescope located in central Mexico at the La Luz Observatory of the University of Guanajuato. The 1.2 m telescope is fiber‐coupled to an ´echelle spectrograph with a spectral resolving power exceeding 20000 over most of the covered spectral range between 3800 Å and 8800 Å, with a small gap of 130 Å around 5800 Å. TIGRE operates robotically, i.e. it (normally) carries out all observations without any human intervention, including, in particular, the target selection in any given observing night. In this paper we describe the properties of the TIGRE instrumentation and its technical realization, as well as our first operational experience with the performance and efficiency of the overall system. Finally, we present some examples of recent TIGRE observations. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)